Evaluating the safety and efficacy of cryopreserved ovarian tissue transplantation in leukemia patients with different bone marrow remission status using xenotransplantation - Li, Yanqiu; Ruan, Xiangyan; Gu, Muqing; Du, Juan; Jin, Fengyu; Cheng, Jiaojiao; Li, Yanglu; Jiang, Lingling; Wang, Zecheng; Yang, Yu; Zhang, Mingzhen; Mueck, Alfred O. (Frontiers in Endocrinology, 2024)
Background Leukemia patients undergoing cryopreserved ovarian tissue transplantation (OTT) may carry a high risk of disease induction. Measurable residual disease (MRD) in bone marrow is linked to an elevated risk of relapse. It is controversial whether leukemia patients must be allowed to achieve measurable residual disease negative (MRD-negative) status instead of measurable residual disease positive (MRD-positive) status before ovarian tissue cryopreservation (OTC). Objective To explore the safety and efficacy of OTT in acute leukemia patients with different MRD status by using xenotransplantation. Method Cryopreserved ovarian tissue from 19 leukemia patients was thawed and xenotransplanted to ovariectomized BALB/C nude mice (n=36). The mice were divided into 2 groups based on the patient’s MRD status before OTC: MRD-negative group (n=18) and MRD-positive group (n=18), additionally, a control group consisted of ovariectomized mice (n=9). Body weight was measured weekly and mortality, emaciation, and other abnormalities were recorded. Twenty-six weeks post-surgery, livers, spleens, uteruses, and ovarian grafts were removed for macroscopic and histological examinations to evaluate the efficacy of xenotransplantation and assess malignant cell contamination in mice. Results Follicle growth was visible in the ovarian grafts of the MRD-negative and MRD-positive groups. Compared with the ovariectomized group, a significant decrease in body weight (p<0.01) was noted, the uterine volume was notably larger, estradiol (E2) levels were significantly higher (p<0.01), and follicle-stimulating hormone (FSH) levels were significantly lower (p<0.001) in the other two groups. Mice in the MRD-positive group showed a significantly higher incidence of death (p<0.001) and emaciation (p<0.01), compared to the MRD-negative group. Histological observation revealed the presence of malignant cells in the grafts, livers, and spleens of 3 mice in the MRD-positive group. No abnormalities were observed in the mice from the MRD-negative group in both macroscopic and histological observations except one mouse was sacrificed for ascites unrelated to leukemia relapse. Conclusion For leukemia patients having ovarian tissue preserved in the first and only centralized human ovarian tissue cryobank in China, immunodeficient mice xenotransplantation can be a method to evaluate the safety and efficacy of OTT; the risk of malignant cell reimplantation due to OTT is higher in leukemia patients with MRD-positive status than those with MRD-negative status before OTC.